Przedszkola w debacie polityczno-oświatowej Niemiec. W stronę edukacji, opieki i wychowania - Inetta Nowosad (Problemy Wczesnej Edukacji)
Contemporary pre-school institutions in Germany have ceased to be perceived solely as providers of care. Significant importance has been assigned to education and upbringing as equivalent categories. The change in approach is not only apparent in their organisation and functioning, but also in state policies, which clearly emphasise the importance of early childhood. The aim of the article is to analyse the political-pedagogical debate that has been in progress since 2005, as well as to scrutinise the adopted arguments and their consequences in the form of the ever changing early school education and care in Germany. The analysis of conditions that have contributed to bestowing preschools with such significance, not only in the process of early childhood development, but also in the process of more broadly understood social development, has also been recognised as equally important, as a result of which preschool institutions have gained importance in the area of political investment that is equal to that granted to schools. The analysis of educational reports and formal-legal guidelines on both federal and state levels is meant to illustrate the range of the introduced changes and the specifics of the German reform, which is perceived as an interlinked network and as cooperation for the sake of children and their families.